2017
DOI: 10.1016/j.jconrel.2017.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Diels Alder-mediated release of gemcitabine from hybrid nanoparticles for enhanced pancreatic cancer therapy

Abstract: Hybrid nanoparticles (HNPs) have shown huge potential as drug delivery vehicles for pancreatic cancer. Currently, the first line treatment, gemcitabine, is only effective in 23.8% of patients. To improve this, a thermally activated system was developed by introducing a linker between HNPs and gemcitabine. Whereby, heat generation resulting from laser irradiation of the HNPs promoted linker breakdown resulting in prodrug liberation. In vitro evaluation in pancreatic adenocarcinoma cells, showed the prodrug was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…Physicochemical properties of GEM do not allow an electrostatic interaction with all nanoparticle surface. For this reason, in previous studies, GEM was grafted onto iron‐oxide nanoparticles by cycloaddition through Diels Alder reaction …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicochemical properties of GEM do not allow an electrostatic interaction with all nanoparticle surface. For this reason, in previous studies, GEM was grafted onto iron‐oxide nanoparticles by cycloaddition through Diels Alder reaction …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Oluwasanmi et al have studied the process of loading of GEM onto hybrid iron oxide‐nanoparticles (HNPs) by Diels Alder reaction . This formulation was capable of high drug loading (86%) which appeared stable even upon reduction of pH and provided to a rapid liberation of the prodrug at elevated temperatures, through retro Diels Alder breakdown . Previously Li et al have obtained a drug loading of about 55% after self‐assembled of GEM onto Diphosphate‐PEG based gadolinium nanoparticles (GdNPs) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively new type of nanoparticle that has been reported with potential in this area is hybrid iron oxide-gold nanoparticles (HNPs) [11,12]. HNPs have been reported to be efficient as drug carriers in pancreatic cancer therapy, where they guide the drug of choice into the cell via endocytosis—thus resulting in larger quantities of internalised drugs compared with the unformulated molecules [13,14]. Previously, we have reported that cytochrome C can become irreversibly bound onto the surface of these HNPs via dative covalent linkage between the gold surface of the HNP and a thiol (-SH) residue in the cytochrome C [12].…”
Section: Introductionmentioning
confidence: 99%
“…HNP synthesis has been well reported previously [23,24,25]. Briefly, iron oxide (Fe 3 O 4 ) nanoparticles were prepared through a precipitation reaction and stabilised with poly(ethylenimine) (MW 200,000).…”
Section: Methodsmentioning
confidence: 99%